Acceleration of Local Revenue through Parking Subscription Policy Innovation: An Implementation Analysis at the Transportation Agency of Sampang Regency - Febrin Aisha Indah; Eny Haryati; Sapto Pramono (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the implementation of the parking subscription policy at the Transportation Agency of Sampang Regency as an effort to accelerate Local Own-Source Revenue (PAD). The parking subscription policy is an institutional innovation that integrates parking levy payments with the annual Motor Vehicle Tax (PKB) payment mechanism at SAMSAT, allowing vehicle owners to pay once a year and access all designated parking facilities. This study employs a descriptive qualitative approach using George C. Edwards III policy implementation framework, encompassing four variables: communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews, field observation, and documentation, with informants purposively selected from the Transportation Agency, Regional Revenue Agency (Bapenda), SAMSAT, parking officers, and community members. The findings reveal that the realization of parking subscription levies has increased from 85.12% in 2020 to 95.37% in 2024. However, implementation still faces obstacles across all four variables: communication inconsistencies at the operational level, limited human resources and information technology infrastructure, a disposition gap between leadership and field officers, and fragmented inter-agency coordination. The study concludes that strengthening the communication system, integrating inter-agency databases, establishing performance-based incentive schemes, and forming a unified coordination team are strategic measures urgently needed to optimize the contribution of the parking subscription policy to the sustainable acceleration of Sampang Regency local revenue.